PELATIHAN MANAJEMEN KEUANGAN SEDERHANA UNTUK MENINGKATKAN DAYA SAING UMKM DI ERA DIGITAL - Olivia, Olivia; Fauzan, Muhammad; Lubis, Taufiqurrahman; Damayanty, Prisila (PUAN INDONESIA, 2025)
Simple financial management training is a strategic step to increase the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in the digital era. Many MSMEs face challenges in managing finances, such as sloppy record keeping, lack of understanding about cash flow, and lack of access to financial technology. This training aims to equip MSME players with basic skills in financial management, including digital financial recording, budget planning and simple investment strategies. By understanding this concept, MSMEs can increase operational efficiency, grow profits, and be better prepared to face competition in the digital market. The implementation of technology-based training also supports the digital transformation of MSMEs, enabling them to be more adaptive to economic developments.